2002
DOI: 10.1037/h0087382
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cue-task association and location on switch cost and alternating-switch cost.

Abstract: Task-switching performance is strongly influenced by whether the imperative stimulus uniquely specifies which task to perform: Switch cost is substantial with bivalent stimuli but is greatly reduced with univalent stimuli, suggesting that available contextual information influences processing in task-switching situations. The present study examined whether task-relevant information provided by task cues influences the magnitude of switch cost in a parallel manner. Cues presented 500 ms prior to a trivalent sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
91
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(108 citation statements)
references
References 37 publications
16
91
1
Order By: Relevance
“…In the experiment conducted by Dreher and Berman (2002), the N Á2 repetition cost was found, but a possible N Á1 shift cost was not reported. Finally, the study of Arbuthnott and Woodward (2002) demonstrated robust N Á1 shift cost under all conditions, whereas the N Á2 repetition cost occurred only under some conditions. Taken together, it seems that there is no consistent data pattern with respect to the occurrence of N Á1 shift cost and NÁ2 repetition cost.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…In the experiment conducted by Dreher and Berman (2002), the N Á2 repetition cost was found, but a possible N Á1 shift cost was not reported. Finally, the study of Arbuthnott and Woodward (2002) demonstrated robust N Á1 shift cost under all conditions, whereas the N Á2 repetition cost occurred only under some conditions. Taken together, it seems that there is no consistent data pattern with respect to the occurrence of N Á1 shift cost and NÁ2 repetition cost.…”
Section: Discussionmentioning
confidence: 82%
“…We are aware of six other studies in which task repetitions occurred in experiments with three tasks, and which thus are relevant to explore the influence of task repetitions on N Á2 repetition cost (Arbuthnott & Frank, 2000;Arbuthnott & Woodward, 2002;Dreher & Berman, 2002;Mayr, 2001Mayr, , 2002Mayr & Keele, 2000). Three of these studies (Mayr, 2001(Mayr, , 2002Mayr & Keele, 2000) report finding N Á1 shift cost and NÁ2 repetition cost.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that transparent cues produce smaller switch costs than nontransparent cues (Arbuthnott & Woodward, 2002;Logan & Bundesen, 2004;Mayr & Kliegl, 2000;Miyake, Emerson, Padilla, & Ahn, 2004). The present investigation attempted to distinguish between two explanations of the difference in switch costs between transparent and nontransparent cues: association strength and mediated retrieval.…”
mentioning
confidence: 88%